GLOBAL TRENDS IN THE IMPLEMENTATION OF ENVIRONMENTAL INNOVATIONS - SHI, Xiaoxi (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article addresses the issues of implementing environmental innovations at the global level. The study aims to analyze the practical experience of introducing environmental innovations based on the assessment of global and European trends, as well as to explore the possibilities of adapting the best international practices to the conditions of Ukraine. The article examines current global trends in the implementation of environmental innovations in the industrial sector, highlighting them as a powerful driver for ensuring sustainable development and economic competitiveness. Environmental innovations are presented as a crucial element of strategies to mitigate environmental impact, ensure long-term economic resilience, foster social responsibility, and enhance overall competitiveness in the context of global economic transformation. The study provides an analysis of the dynamics of the Eco-Innovation Index in European Union countries for 2014–2024, which enables the identification of priority directions for green transformation and the detection of regional asymmetries in innovation activity. The research substantiates the role of environmental innovations in minimizing anthropogenic impact on the environment, increasing energy efficiency, and developing renewable energy sources. The structure of the European Investment Bank’s investments in 2024 is analyzed, revealing a strategic focus on financing energy decarbonization, green infrastructure, resource-efficient technologies, and low-carbon transport. Successful practices of integrating environmental innovations are identified, using Finland as an example, including the development of wind energy, bioeconomy, hydrogen technologies, and digital platforms for the life cycle assessment of products. The findings show that the comprehensive combination of financial instruments, government support, institutional reforms, and high-tech solutions creates the prerequisites for forming green value chains and strengthening countries’ positions in the global market. The article proposes directions for adapting Finland’s experience in Ukraine, with an emphasis on the development of renewable energy, bioeconomy, and digital solutions for environmental management.